A case study of the flipped classroom approach for translation studies in Vietnam - Nguyen, Quang Nhat (2021)
Traditional methods of lecture-based teaching are still pervasive in many Vietnamese translation courses at Higher Education (Pham, 2016). This study presents an alternative, practical and a more efficacious way to improve the quality of translation training in Vietnam. It examines a novel flipped classroom approach aimed at providing dynamic and novel instructional learning of two Translation modules in a Vietnamese public university. The alternative approach inverts the traditional teacher-learner roles, and makes it culturally-appropriate and contextually-relevant to the local context. This approach was adapted from the three-stage framework of Zhai et al. (2017), taking careful consideration of all the relevant factors within the implementation process based on Activity theory. Using a case-study research design proposed by Yin (2014), this study aims to: